2022
DOI: 10.1038/s41423-022-00919-5
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-specific inhibition of the histone demethylase JMJD3 decreases STING and pathologic inflammation in diabetic wound repair

Abstract: Macrophage plasticity is critical for normal tissue repair following injury. In pathologic states such as diabetes, macrophage plasticity is impaired, and macrophages remain in a persistent proinflammatory state; however, the reasons for this are unknown. Here, using single-cell RNA sequencing of human diabetic wounds, we identified increased JMJD3 in diabetic wound macrophages, resulting in increased inflammatory gene expression. Mechanistically, we report that in wound healing, JMJD3 directs early macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 79 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…The M2-Exo release profile, antibacterial evaluation, and biocompatibility assessment of FM-Exo hydrogel were evaluated as detailed in SI Section S1. 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The M2-Exo release profile, antibacterial evaluation, and biocompatibility assessment of FM-Exo hydrogel were evaluated as detailed in SI Section S1. 4.…”
Section: Methodsmentioning
confidence: 99%
“…These factors collectively contribute to the challenges in achieving an efficient wound closure. The continuous inflammation delays the progression from inflammation to proliferation, representing a crucial mark that influences the proper healing of diabetic wounds. Furthermore, the capacity of cells to proliferate and migrate is suppressed due to the numerous released inflammatory cytokines, including tumor necrosis factor (TNF)-α and interleukin (IL)-6. Macrophages (Mφ) are one of the key immune cells regulating the process of inflammation, which can be activated and polarized into different phenotypes that are mainly classified as the classical-activated M1 phenotype showcasing pro-inflammation and alternative-activated M2 phenotype possessing anti-inflammation capacity .…”
Section: Introductionmentioning
confidence: 99%
“…A potential therapy was found and con rmed that interferon (IFN) regulates Setdb2 expression in wound macrophages via type 1 interferon/janus kinase/signal transducer and activator of transcription 1 (IFN-1/JAK/STAT1) signaling, which promotes the transformation of macrophages from in ammation to repair and is bene cial for wound healing [99]. Interestingly, another study found that the increased expression of in ammatory genes was associated with the Jumonji domain-containing protein D3 (JMJD3) production in macrophages from diabetic wounds [100]. During the late stage of wound injury, IL-6 increases, regulating JMJD3 expression in macrophages through JAK1, while the increase expression of 3/STAT3 pathway and JMJD3 in late process can induce the NF-κB mediated transcription of in ammatory genes in macrophages by in uencing H3K27me3 [100].…”
Section: Antioxidant Therapy and Nf-κb Pathwaymentioning
confidence: 99%
“…Interestingly, another study found that the increased expression of in ammatory genes was associated with the Jumonji domain-containing protein D3 (JMJD3) production in macrophages from diabetic wounds [100]. During the late stage of wound injury, IL-6 increases, regulating JMJD3 expression in macrophages through JAK1, while the increase expression of 3/STAT3 pathway and JMJD3 in late process can induce the NF-κB mediated transcription of in ammatory genes in macrophages by in uencing H3K27me3 [100]. Further, the study showed that macrophage-speci c nanoparticles were effective at inhibiting JMJD3 in diabetic wounds, as well as reducing in ammation and accelerating wound healing [100].…”
Section: Antioxidant Therapy and Nf-κb Pathwaymentioning
confidence: 99%
See 1 more Smart Citation